Knowing-cognitive component of future teachers‟ professional training in the European educational space - Halyna Boryn (Vasyl Stefanyk Precarpathian National University, 2017)
The ways of knowing-cognitive component's improvement of future educators' trainingof preschool educational institutions in higher educational institution are analyzed in thearticle and optimal pedagogical approaches to personal development of a student in the studyof normative educational disciplines are outlined. Key words: training of teachers, educational-consultative interaction, knowing-cognitivecomponent, content of education.